ENSURING THE QUALITY OF THE EDUCATIONAL PROCESS IN THE CONDITIONS OF MIXED EDUCATION OF FUTURE SPECIALISTS (Innovative professional education, 2024)
An important indicator of the demand for educational services and the competitiveness of specialists trained by an educational institution is the quality of education, which is revealed as the level of compliance of training results with the requirements of society and the state economy. The quality of education is ensured by creating a safe educational environment; the presence of a transparent and understandable system for evaluating educational achievements of education seekers; organization of effective activities of teaching staff and constructive management activities of the administration of the educational institution
Keywords: quality of education, effective methods of blended learning, effective pedagogical activity, informational interaction of participants in the educational process